Organic-inorganic hybrid materials for green photonics: luminescent solar concentrators - Correia, Sandra Filipa Henriques (2017)
Luminescent solar concentrators are inexpensive devices that aim to increase the efficiency of photovoltaic cells and promote the urban integration of photovoltaic devices, with unprecedented possibilities of energy harvesting through the façade of buildings, urban furniture or wearable fabrics. Generally, they consist of a transparent matrix coated or doped with active optical centres that absorb the incident solar radiation, which is re-emitted at a specific wavelength and transferred by total internal reflection to the edges where the photovoltaic cells are located. The main objective of this work is the production of luminescent solar concentrators whose optically active layer is based on organic-inorganic hybrid materials doped with europium ions or organic dyes, in particular, Rhodamine 6G and Rhodamine 800. Rhodamine 800, as opposed to europium ions and Rhodamine 6G which emit in the visible range, emits in the near infrared (NIR) range, which is an advantage for crystalline Si-based photovoltaic cells, whose efficiency is greater in the NIR. In this work, although the luminescent solar concentrators with planar geometry are addressed, the main focus is the use cylindrical geometry. The use of this type of geometry allows the effect of concentration to be higher relative to the planar geometry, since the ratio between the exposed area and the area of the edges is increased. The cylindrical geometry is exploited by producing luminescent solar concentrators based on polymer optical fibre (plastic) where the optically active layer is on the outside (as a coating) or inside (as a filling in the hollow core) of the optical fibre. Furthermore, the possibility of increasing the exposed area was also dealt with the production of bundles of luminescent solar concentrators in which the plastic optical fibres are placed side by side and, also, by fabricating luminescent solar concentrators with length in the metre scale.